MONITORING OF ORIENTAL FRUIT MOTH WITH SYNTHETIC SEXUAL PHEROMONE IN STATE OF PARANÁ - POLTRONIERI, Alex Sandro; SILVA, Éder David Borges da; MONTEIRO, Lino Bittencourt (Scientia Agraria, 2008)
The oriental fruit moth, Grapholita molesta, is one of the main pest of fruit trees from tempered climate, damaging fruits and shoots of stone and pome fruits. Currently the monitoring of this insect is made with synthetic pheromone traps, however, it is not registered for use in the State of the Paraná. The objective of this work was to compare the attractiveness of the synthetic sexual pheromone of G. molesta with the pheromone produced by virgin females reared in laboratory conditions. The experiment was carried out in Porto Amazonas, PR, in an orchard of ‘Imperial Gala' apple trees, where synthetic BioGrapholita® and virgin females had been installed in Delta traps. The traps with synthetic sexual pheromone were more efficient, capturing more than 90% of the moth.